ԿՐՏՍԵՐ ԴՊՐՈՑԱԿԱՆԻ ԻՆՔՆՈՒՐՈՒՅՆՈՒԹՅԱՆ ԱՌԱՆՁՆԱՀԱՏԿՈՒԹՅՈՒՆՆԵՐԸ ՀԵՌԱՎԱՐ ԿՐԹՈՒԹՅԱՆ ՊԱՅՄԱՆՆԵՐՈՒՄ - Հակոբյան, Ս․; Խանամիրյան, Ի․Ռ․ (Արդի հոգեբանություն, 2022)
This article reflects the concepts of teachers and parents about the independence of primary schoolchildren in the context of the 2020 pan- demic. A comparative analysis is given between the characteristics and types of independence (activity, criticality and flexibility of thinking, independent homework, dependence on parents when performing various tasks, etc.) in the conditions of distance and full-time education. Independence is especially important at primary school age, when educational activity becomes dominant. The study is aimed at studying the characteristics of the independence of primary schoolchildren, for whom the transition to distance learning has become especially critical, given their age characteristics. According to the hypothesis, it is assumed that, in contrast to full-time education, distance learning contributes to the development of the independence of primary school children. An expert survey was conducted using 2 questionnaires. The research results are presented in the form of corresponding conclusions. In general, it can be stated that distance learning negatively affects the activity, self-confidence and independence of primary school children.
Keywords: ինքնուրույնություն; ակտիվություն; ուսումնական գործընթաց; հեռավար կրթություն